2015
DOI: 10.1016/j.anbehav.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone might not be necessary to support female aggression in incubating northern cardinals

Abstract: Keywords: aggressionCardinalis cardinalis corticosterone female incubation maternal aggression nest defence northern cardinal testosterone Testosterone's (T) influence on male aggression has been well established in many vertebrate species, but the impact of T on female aggressive behaviour is poorly understood. Among birds, a link between T and female aggression is plausible, as females of many species exhibit a seasonal peak in T concentrations at the onset of breeding when social instability is greatest and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…The link between plasma androgen levels and intra-sexual competition has been extensively studied under the “challenge hypothesis” [21], which states that, during reproduction, plasma T correlates positively with male-male competition. In females, although there are fewer studies than in males, similar hormonal responses to social challenges have been observed [16, 18, 22, 23], yet studies have also reported no link, or even negative correlations between female-female competition and circulating plasma androgen levels [19, 2427]. Given these contradictory findings, further research is required to clarify the relationship between intra-sexual competition and circulating androgens in females.…”
Section: Introductionmentioning
confidence: 99%
“…The link between plasma androgen levels and intra-sexual competition has been extensively studied under the “challenge hypothesis” [21], which states that, during reproduction, plasma T correlates positively with male-male competition. In females, although there are fewer studies than in males, similar hormonal responses to social challenges have been observed [16, 18, 22, 23], yet studies have also reported no link, or even negative correlations between female-female competition and circulating plasma androgen levels [19, 2427]. Given these contradictory findings, further research is required to clarify the relationship between intra-sexual competition and circulating androgens in females.…”
Section: Introductionmentioning
confidence: 99%
“…In the Northern Cardinal past work has found that carotenoid-based plumage ornaments can indicate body size and condition ; however, this has not been the case for melanin-based ornaments. Furthermore, neither size nor condition has been found to covary with hormone production (Jawor 2007, DeVries et al 2011, territory and nest defense (DeVries et al 2012(DeVries et al , 2015, or parental care behavior , DeVries and Jawor 2013 in the Northern Cardinal. Previous findings concerning condition, size, and behavior are from both the current study population in Mississippi and the Ohio population previously studied and suggest that body size and condition may not play a strong factor in aggressive behavior in this species.…”
Section: Discussionmentioning
confidence: 98%
“…Intrasexual aggressive behavior was assessed using an SNI based on methods described in and modified slightly based on DeVries et al (2015). On the day of SNI assessment, between 0600 and 1000 hr, a female Northern Cardinal decoy (mounted in a perching posture) was placed 1 m from the nest of a focal female after the focal female had left for a break in incubation.…”
Section: Simulated Nest Intrusions (Snis)mentioning
confidence: 99%
“…In the Northern Cardinal past work has found that carotenoid-based plumage ornaments can indicate body size and condition ; however, this has not been the case for melanin-based ornaments. Furthermore, neither size nor condition has been found to covary with hormone production (Jawor 2007, DeVries et al 2011, territory and nest defense (DeVries et al 2012(DeVries et al , 2015, or parental care behavior , DeVries and Jawor 2013 in the Northern Cardinal. Previous findings concerning condition, size, and behavior are from both the current study population in Mississippi and the Ohio population previously studied and suggest that body size and condition may not play a strong factor in aggressive behavior in this species.…”
Section: Discussionmentioning
confidence: 98%
“…Here, we investigated how a melanin-pigmented plumage ornament, the face mask, covaries with intrasexual aggression in female Northern Cardinals (Cardinalis cardinalis). Female cardinals display both intrasexual and intersexual aggression over territories and nesting resources , DeVries et al 2015. In female cardinals, previous work found that face mask expression co-varied with aggressive behavior at the nest ).…”
Section: Introductionmentioning
confidence: 99%